Investigation of the anti-Huanglongbing effects using antimicrobial lipopeptide and phytohormone complex powder prepared from Bacillus amyloliquefaciens MG-2 fermentation - Ding, Zhicheng; Liu, Yang; Zhang, Shaoran; Wang, Fangkui; Zong, Qi; Yang, Yuehua; Du, Anna; Zheng, Yajie; Zhu, Jian; Jiang, Ling (Frontiers in Microbiology, 2024)
Global citrus production has been severely affected by citrus Huanglongbing (HLB) disease, caused by Candidatus Liberibacter asiaticus (Clas), and the development of effective control methods are crucial. This study employed antimicrobial lipopeptide and phytohormone complex powder (L1) prepared from the fermentation broth of the endophytic plant growth promoting bacterium (PGPB) of Bacillus amyloliquefaciens strain MG-2 to treat Candidatus Liberibacter asiaticus (CLas)-infected ‘Citrus reticulata ‘Chun Jian’ plants. Real-time fluorescence quantitative polymerase chain reaction (qPCR) and PCR were employed for disease detection. The results revealed that after 15 spray-drench treatments with L1 solution, the HLB infection rate decreased from 100 to 50%, the bacterial titer decreased by 51.9% compared with a 27.9% decrease in the control group. L1 treatment triggered the production of reactive oxygen species, increased lignin content, and increased defense enzyme activities (p < 0.05). Defense-related gene expression significantly increased within 12 h of treatment. In addition, L1 application also promoted plant growth, as evidenced by higher transpiration rates and net photosynthetic rates as well as increased leave or root density. Root flora analysis revealed that the abundances of Burkholderia_thailandensis, unclassified_g_Burkholderia-Caballeronia-Paraburkholderia, unclassified_g__Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium, and Pseudomonas_mosselii were 1.64, 1.46, 5.84, and 6.93 times greater, respectively, than those in the control group. The levels of phenylpropanoids, polyketides, lipids, lipid-like molecules, organic acids, and derivatives, significantly increased following L1 treatment (FC > 2, p < 0.05). Additionally, salicylic acid, dihydrojasmonic acid, and isopentenyl adenosine levels in leaves markedly increased. High-performance liquid chromatography (HPLC) confirmed that L1 contained surfactin, iturin and fengycin cyclic-lipopeptides (CLPs) as well as indole-3-acetic acid (IAA), 3-indolebutyric acid (IBA), indole-3-carboxylic acid and indole-3-carboxaldehyde auxins, N6-entopentenyladenine and t-zeatin-riboside cytokinins, abscisic acid, 1-aminocyclicpanecarboxylic acid, salicylic acid, and gibberellin A1, A3 and A4 phytohormones. These findings provide insight into multiple mechanisms by which endophytic Bacillus PGPB L1 is able to combat HLB disease, to promote citrus plant growth, and to optimize the root flora for soil health which offering an innovative strategy for sustainable management of this severe disease and improving citrus plant growth and productivity